A density functional study of Br on Cu(100) at low coverages - Kenny, S; Pethica, J; Edgell, R (2003)
Density functional theory has been used to study the adsorption of Br on Cu(1 0 0) at low coverages. As expected, the most stable binding site for Br atoms is the fourfold hollow site. The barrier for Br hopping between adjacent hollow sites along 〈0 1 1〉 directions via twofold saddle points is estimated to be 0.23 eV, whereas the barrier for hopping along 〈0 1 0〉 directions via an on-top site is 0.37 eV. The low barriers for motion between hollow sites indicate that it should not be possible to image low coverages of Br on Cu(1 0 0) at room temperature in scanning tunnelling microscopy. It is suggested that features previously attributed to Br atoms in hollow sites should in fact be assigned to Br bound in surface copper vacancy sites. © 2002 Elsevier Science B.V. All rights reserved.